Health and beliefs of the Roma in Europe: a review - María Gemma Tuset Garijo; Alba Roca Biosca; Pilar Alamillo Pérez-Grueso; María Antonia Martorell Poveda (Universidad de Alicante, 2013)
Introduction: The Roma community is the largest ethnic minority in Spain, Central and Eastern Europe. As an ethnic group is characterized by a series of cultural elements that shape its ethnic content, its own cultural baggage that distinguishes it from other groups with which it comes into contact. Provide health care services that generally do not address cultural considerations. Aim: to have a greater understanding of the health of the European Roma and his personal view on the concept of health and illness in order to provide an effective tool to help nurses to provide proper care from a multicultural perspective. Method: In the first search was conducted a review of the literature published over the past 30 years in the databases PubMed, Cuiden, Scopus, Cinalh, Index, Spanish physician, ISOC-CSIC and multicercador URV. In a second search used the metasearch "google.com" and "metacrawler.com". Results: We found 102 articles related to the subject to revision of which 13 were considered crucial for providing useful information relevant to the review study. The topics covered were referring to genetic diseases, to sociology and anthropology of health care, child health and transmissible diseases.